Mobile Health Upaya Peningkatan Kepatuhan Pengobatan Pasien Anak dengan Tuberkulosis : Tinjauan Literatur - Tanjung, Syarifah Aini; Wildani, Andi Amalia (Universitas Fort De Kock Bukittinggi, 2021)
Background: Children are at risk for severe symptoms of tuberculosis. Most tuberculosis drug formulations have poor acceptance in children and require consistent adherence over a long period of time. The mobile-health application is a technology that can reach various levels of society, which is useful in the management of adherence to treatment of children with TB. Objective: To provide an overview and ideas about the application of the m-health system in Indonesia, especially in the area of nursing children with tuberculosis. Method: Literature review is a study conducted to analyze the literature that has been selected from various sources to become a conclusion of a new idea. Discussion: The m-health application is effectively used for nursing services for children, especially children who are being treated for tuberculosis. In the development of m-health technology, regulations and legal policies are needed to enable the application and integration of m-health technology with health services. Recommendation: It is hoped that further research can make m-health applications to improve medication adherence in children with tuberculosis and test its effectivenessKeywords: mobile health, medication adherence, TB in children